Prognostic impact of invasive hemodynamic evaluation in patients with pulmonary arterial hypertension - Ricardo, I. Aguiar (2018)
Published on behalf of the European Society of Cardiology. All rights reserved. © The Author 2017. For permissions, please email: journals.permissions@oup.com.